More or less equal? Trends in horizontal equity in mental health care utilization in Stockholm county, Sweden (2006–2022). Repeated survey-registry linked studies - Joseph Junior Muwonge; Beata Jablonska; Christina Dalman; Bo Burström; Maria Rosaria Galanti; Anna-Clara Hollander (International Journal for Equity in Health)
Abstract Background Horizontal equity is defined as equal care for equal needs, regardless of socioeconomic factors. This study investigated trends in horizontal equity in mental health care (MHC) utilization in Sweden from 2006 to 2022. Monitoring equity provides valuable information for healthcare system governance (e.g., planning and resource allocation) necessary for ensuring equitable provision of services. Methods A total of 81,650 Stockholm residents aged 18–64, who participated in the Hälsa Stockholm surveys of 2006, 2010, 2014 or 2021, were analysed. Their subsequent use of MHC (primary, in- and outpatient specialized care, and psychotropic medication) within six months after survey response was collected from registries between 2006 and 2022. Concentration index (CI) and need-standardized CI (Horizontal inequity index, HI), summative measures of inequalities, were used in this study. HI was estimated using self-reported psychological distress (measured with the General health questionnaire 12 in 2006–2014 and Kessler 6 in 2021) as the primary need indicator, with general health status and long-term limiting illness as additional need indicators. Equivalized disposable household income was used as the ranking variable, while education status, migration status, age, and sex were included as non-need variables that we controlled for in the analyses. Results Lower-income individuals used MHC services more than their higher-income counterparts with comparable levels of psychological distress. These “pro-poor” inequities in the probability of MHC use increased from HI = -0.057 [95% Confidence Limits, CL: -0.079, -0.034] in 2006/2007 to HI = -0.130 [95% CL: -0.159, -0.102] in 2014/2015. By 2021/2022, the “pro-poor” inequities had decreased (HI = -0.034 [95% CL: -0.06, -0.009]), partly due to an increase in MHC use among higher-income groups but a decrease in the lowest income group. Standardizing for additional need indicators reduced the “pro-poor” inequities but maintained the observed trends. Among non-Nordic migrants, “pro-rich” inequities fell between 2006/2007 and 2014/2015 but rose in 2021/2022, with significant “pro-rich” inequities among non-European migrants in 2021/2022 (HI = 0.100 [95% CL: 0.024, 0.176]). Among patients in outpatient services, “pro-poor” inequities in visit frequency decreased over time (2006–2022). Conclusion We observed increasingly higher probability of MHC use among lower-income individuals than their higher-income peers with similar (measured) needs from 2006 to 2015. However, during the pandemic (2021/2022), potential access problems led to diminishing of “pro-poor” inequities in the total sample, and to “pro-rich” inequities among non-Nordic migrants. The Covid-19 disruption to the healthcare system—such as restrictions on in-person visits and the rapid transition to digital healthcare services—along with its impact on care-seeking, may explain the trend shifts.